Systematic Review and Network Meta-Analysis: Comparative Efficacy and Safety of Biosimilars, Biologics and JAK1 Inhibitors for Active Crohn Disease - Guozhi Wu; Guozhi Wu; Guozhi Wu; Yuan Yang; Yuan Yang; Yuan Yang; Min Liu; Min Liu; Yuping Wang; Yuping Wang; Qinghong Guo; Qinghong Guo (Frontiers Media S.A., 2021)
Background: Crohn disease (CD) is a chronic inflammatory disease that affects quality of life. There are several drugs available for the treatment of CD, but their relative efficacy is unknown due to a lack of high-quality head-to-head randomized controlled trials.Aim: To perform a mixed comparison of the efficacy and safety of biosimilars, biologics and JAK1 inhibitors for CD.Methods: We searched PubMed, Web of Science, embase and the Cochrane Library for randomized controlled trials (RCTs) up to Dec. 28, 2020. Only RCTs that compared the efficacy or safety of biosimilars, biologics and JAK1 inhibitors with placebo or another active agent for CD were included in the comparative analysis. Efficacy outcomes were the induction of remission, maintenance of remission and steroid-free remission, and safety outcomes were serious adverse events (AEs) and infections. The Bayesian method was utilized to compare the treatments. The registration number is CRD42020187807.Results: Twenty-eight studies and 29 RCTs were identified in our systematic review. The network meta-analysis demonstrated that infliximab and adalimumab were superior to certolizumab pegol (OR 2.44, 95% CI 1.35-4.97; OR 2.96, 95% CI 1.57-5.40, respectively) and tofacitinib (OR 2.55, 95% CI 1.27-5.97; OR 3.10, 95% CI 1.47-6.52, respectively) and revealed the superiority of CT-P13 compared with placebo (OR 2.90, 95% CI 1.31-7.59) for the induction of remission. Infliximab (OR 7.49, 95% CI 1.85-34.77), adalimumab (OR 10.76, 95% CI 2.61-52.35), certolizumab pegol (OR 4.41, 95% CI 1.10-21.08), vedolizumab (OR 4.99, 95% CI 1.19-25.54) and CT-P13 (OR 10.93, 95% CI 2.10-64.37) were superior to filgotinib for the maintenance of remission. Moreover, infliximab (OR 3.80, 95% CI 1.49-10.23), adalimumab (OR 4.86, 95% CI 1.43-16.95), vedolizumab (OR 2.48, 95% CI 1.21-6.52) and CT-P13 (OR 5.15, 95% CI 1.05-27.58) were superior to placebo for steroid-free remission. Among all treatments, adalimumab ranked highest for the induction of remission, and CT-P13 ranked highest for the maintenance of remission and steroid-free remission.Conclusion: CT-P13 was more efficacious than numerous biological agents and JAK1 inhibitors and should be recommended for the treatment of CD. Further head-to-head RCTs are warranted to compare these drugs.